The circle - Panahi, Jafar; Partovi, Kambozia (New York : Fox Lorber Films, 2001)
This film offers insights into the lives of women in Iran. As the narrative dynamically shifts from woman to woman, their stories culminate with tremendous potency, transforming a shared sense of despair and injustice into hope.
Bonus features described in detail on cover.
Originally released as a motion picture in 2000 under title: Dayirah.
Director, Jafar Panahi ; screenplay, Kambozia Partovi.
Nargess Mamizadeh, Maryam Parvin Almani, Mojgane Faramarzi, Elham Saboktakin, Monir Arab, Solmaz Panaki, Fereshteh Sadr Orafai, Fatemah Naghavi.
DVD.
In Farsi with English subtitles.
Keywords: Feature films; Foreign films -- Iran; Women -- Iran -- Social conditions